Regulated Nitrooxidation Process with the Formation of a Developed Diffusion Zone - Eshkabilov, Kholikul (Current Approaches in Engineering Research and Technology Vol. 5, 2024)
In order to improve the physical and mechanical properties of cutting tools made of P6M5 steel, the article presents the results of a study of the possibility of using a combined method of nitrooxidation, consisting of nitriding in ammonia at the first stage and oxidation in water vapor at the second stage. The formation of nitride-oxide coating compositions with the formation of a thin dense oxide film and a nitride layer under it, depending on the holding time, undergoes structural and phase transformations during the oxidation process with the transition of low nitrides doped with carbon and oxygen, as well as an internal nitriding zone following it. It has been established that during the oxidation process, an oxide layer with a nitride sublayer or zones of internal nitriding with supersaturated nitrogen can be formed on the surface, allowing the production of stable nitrides of both the base metal and alloying elements. By regulating the parameters of the nitrooxidation process on alloyed steels, compositions with different structural and phase states can be formed that have the best physical and mechanical properties than the nitride layer obtained by traditional nitriding methods. For surface hardening of cutting tools, it is necessary to obtain a nitride-oxide layer with a thin oxide layer on the surface and a nitride sublayer consisting of low-nitrogen nitrides alloyed with carbon and oxygen with a developed sublayer of the internal nitriding zone. The oxide layer, together with the subsequent arrangement of the nitride layer on the surface of the internal hardness nitriding zone, successfully provides a positive gradient of surface properties under external friction conditions and has the best ductility in terms of ensuring wear resistance.